The Effect of the Application of Interprofessional Education (IPE) Simulation Using Role Model Method Towards the Knowledge and Attitude of Nursing Undergraduate Students in Universitas Islam Sultan Agung - Stevany Kii Londong, Refenia; Hadromi, Hadromi; Haryadi, Bambang (Universitas Negeri Semarang, 2019)
The lack of knowledge and attitude of the students toward interprofessional education make the students have a hard time to communicate effectively because they come from different health program, need an approach and knowing the habit of the other students that they will communicate to and work with in increasing the health service. The aims of this study are (1) analyzing the effect of the application of interprofessional education simulation using role play towards the knowledge improvement about the interprofessional education for the nursing undergraduate students in Unissula, (2) analyzing the effect of the application of interprofessional education simulation using role play towards the attitude about interprofessional education for the nursing undergraduate students in Unissula. Quasi-experimental methods was used in this study. This quasi-experimental research design is pre-test and post-test without control group. The instruments used in this research were questionnaire. The type of the questionnaire was the closed questionnaire which was a questionnaire with provided answer. The data analysis used in this research was paired sample t-test analysis by doing analysis towards the pre-test and post-test. The result of validity test by using product moment correlation in the application of interprofessional education using role model method towards the knowledge about interprofessional education for nursing undergraduate students in Unissula was that from 28 items of question in the instrument, there were 3 invalid questions which were the question number 12, 14, and 21. The reliability result by using Alpha Cronbach in the application of interprofessional education using role model method towards the knowledge about interprofessional education for nursing undergraduate students in Unissula was 0.877 from 25 items of question. The validity test result by using product moment correlation in the application of interprofessional education using role model method towards the attitude about interprofessional education for nursing undergraduate students in Unissula was that from 12 items of question, all questions were valid with reliability point of 0.960. The research result show that the usage of interprofessional education using role play method towards the nursing students may improve the student’s knowledge in the effort of increasing the health service that centered on the patient because there are (1) an improvement in the pre-test and post-test result as many as 16.55 for pre-test and 25.82 for post-test; (2) data distribution (standard deviation) in pre-test is 5.370 with the error standard of 0.767; and (3) data distribution in the post-test is 0.486 with error standard of 0.069. Besides, the application of interprofessional education using role play method may affect towards attitude because the average student’s attitude shows the result of satisfying attitude category with 33 students (67.3%) and quite satisfying category with 16 students (32.7%).